Left ventricular unloading with gentle chest compressions for patients on veno-arterial extracorporeal membrane oxygenation: two case reports - Jiang, Lingyu; Huang, Minyan; Xiang, Shulin; Xiong, Bin; Li, Guibin; Zhong, Yonglong; Han, Lin (Frontiers in Cardiovascular Medicine, 2024)
Background Insufficient ventricular unloading is a serious complication during veno-arterial extracorporeal membrane oxygenation (VA-ECMO) that has a crucial impact on patient outcomes. The existing conservative treatment options are limited, while mechanical decompression techniques are challenging and restricted in terms of their adoption and application. Two patients with cardiogenic shock experienced insufficient left ventricular unloading with no pulsatile contraction and aortic valve closure during VA-ECMO support. Gentle chest compression was applied to establish an active left ventricular drainage mechanism, which prevented the formation of intracardiac thrombi. No life-threatening complications or technical problems occurred. Therefore, gentle chest compression was established as an effective and safe method for treating insufficient left ventricular unloading in VA-ECMO patients.